Construction of rechargeable bio-battery cells from electroactive antioxidants extracted from wasted vegetables - Hussain, Z. (Elsevier Ltd, 2021)
This work is focused on energy harvesting and energy storage through renewable sources. In many cases, vegetables may either get rotted or the market gets full due to imbalance in supply, price and demand. The waste vegetables and wild plants contain electrochemically active compounds, which can be used for preparation of rechargeable bio-battery cells. In this study, a set of battery cells was constructed by coupling the electroactive compounds of Onion-Radish, Onion-Bitter Orange, Onion-Cactus, Turnip-Radish, Turnip-bitter orange and Turnip-cactus. The fresh and boiled juices of these vegetables and wild plant combinations were used and the reaction conditions were optimized to maximize the output voltage. The output voltage was measured before and after charging of cells for different charging times, juice volume, charging voltage and pH of cell media. The effect of media was explored by changing the media nature from acidic to neutral and neutral to basic. It was observed that the voltage of most of the cells in basic media is higher than the neutral and basic media. Among the investigated batteries, turnip-cactus single cell battery produced an open circuit voltage of 2.13 V while the onion-radish battery produced an open circuit voltage 1.9 V. Â© 2021 The Authors